Ongoing automated ground deformation monitoring of Domuyo - Laguna del Maule area (Argentina) using Sentinel-1 MSBAS time series: Methodology description and first observations for the period 2015–2020. (December 2020) - Derauw, Dominique; Nicolas, d'Oreye; Jaspard, Maxime; Caselli, Alberto; Samsonov, Sergey
Abstract: Synthetic Aperture Radar (SAR) Differential Interferometry (DInSAR) and its extensions to manage time series are nowadays well-known and mastered techniques to perform among others land-motion monitoring. We present here a fully automated monitoring service based on DInSAR and Multidimensional Small Baseline Subset (MSBAS) methods. The automated processing chain named "InSAR automated Mass processing Toolbox for multidimensional Time series" (MasTer) is demonstrated with the peculiar case of the Laguna del Maule and Domuyo volcanoes, which are known to undergo significant inflation up to several cm or tens of cm per year. The here-described monitoring service is made of three components: an InSAR command line processor, the MSBAS processor and a number of shell scripts automatizing all tasks, from data downloading to updated displacement maps and time series. Thanks to the European Commission Copernicus Service, data are freely available every 12 or 6 days along each orbit, depending on ESA acquisition plan. Linear deformation rate maps and time series of vertical and East-West ground deformation computed by the MasTer tool are updated every 1–6 days on a web page, according to the S1 data availability. Interested user can request additional time series at coherent pixels that wouldn't be displayed on the web page and receive them by e-mail within a minute. Processing chain and preliminary observations at Domuyo and Laguna del Maule test site are presented and commented. The nearly 6 years long 2D time series of ground deformation allow highlighting recent changes in the well-known deformation at both volcanoes: Domuyo inflation stabilizes since beginning of 2019 while deformation at Laguna del Maule seems to gently accelerate since mid 2018. New deformation features are also identified, such as a 2 km wide 3 cm/yr circular subsidence at Laguna del Maule as well as a 2 cm/yr downward and 1 cm/yr eastward movement located to the East of Laguna Fea. Highlights: Fully automatic ground deformation monitoring service based on SAR data. 2D linear deformation maps and time series updated on web page every 1–6 days. Possible web request of time series to be sent by email within a minute. System is illustrated with Sentinel 1 data but can be performed with, or in combination with any other SAR mission. Inflation observed at Domuyo and Laguna del Maule (LdM) volcanic complexes and new deformation features identified at LdM and Laguna Fea.